2019
DOI: 10.1111/jfpe.13051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanolic extraction, thermal vacuum concentration, ultrafiltration, and spray drying on polyphenolic compounds of tropical highland blackberry (Rubus adenotrichos Schltdl.) by‐product

Abstract: Tropical highland blackberry by‐product (BBP) has high amounts of polyphenols including ellagitannins (ET) and anthocyanins (ATC). Information of the effect of different operations on ET is scarce. In this study, pseudo‐first and first order kinetic models and response surface methodology were applied to optimize the extraction of polyphenols from BBP using ethanol, a food grade solvent. Retention of total polyphenols, ET and ATC was analyzed considering their contents before and after the application of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…For the tested pomace variants, the extraction rate constants were on average 40% higher in the first step (0.012 to 0.021 min −1 ) than in the second step (0.0068 to 0.013 min −1 ), except for pomace from the production of wild strawberry puree (0.010 min −1 vs. 0.012 min −1 ). In a study on the kinetics of ET extraction from blackberry byproducts, Quirós et al (2019) obtained an extraction rate constant of 0.079 min −1 , which is in line with the present findings (the extraction rate constant for blackberry pomace in the first step was 0.012-0.021 min −1 ). In terms of the kinetics of total polyphenolic extraction from fruit material, Khan et al (2010) reported a rate constant of 0.03 min −1 for orange peels (also using a first-order model).…”
Section: Extraction Kinetics Of Total Etssupporting
confidence: 91%
See 4 more Smart Citations
“…For the tested pomace variants, the extraction rate constants were on average 40% higher in the first step (0.012 to 0.021 min −1 ) than in the second step (0.0068 to 0.013 min −1 ), except for pomace from the production of wild strawberry puree (0.010 min −1 vs. 0.012 min −1 ). In a study on the kinetics of ET extraction from blackberry byproducts, Quirós et al (2019) obtained an extraction rate constant of 0.079 min −1 , which is in line with the present findings (the extraction rate constant for blackberry pomace in the first step was 0.012-0.021 min −1 ). In terms of the kinetics of total polyphenolic extraction from fruit material, Khan et al (2010) reported a rate constant of 0.03 min −1 for orange peels (also using a first-order model).…”
Section: Extraction Kinetics Of Total Etssupporting
confidence: 91%
“…In terms of the kinetics of total polyphenolic extraction from fruit material, Khan et al (2010) reported a rate constant of 0.03 min −1 for orange peels (also using a first-order model). Similar polyphenolic extraction constants have been reported from studies involving blackberry biomass (0.023 min −1 , Quirós et al 2019) and grapes (0.040 min −1 , Sant' Anna et al 2012). In the present study, the extraction half time t 1/2 did not exceed 1 h for any of the tested raspberry and blackberry pomace variants (in the first step), with a significant slowdown in the ET extraction rate after that time.…”
Section: Extraction Kinetics Of Total Etssupporting
confidence: 81%
See 3 more Smart Citations